EXISTENCE IN THE VILLAGE LANTING HOUSE CAPE COMMERCIAL DISTRICT NANGGA PINOH MELAWI WEST KALIMANTAN - Emi Tipuk Lestari, Mardiana (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Lanting house is a house that floats on water, because it is supported by bonding bamboo or timber as a buffer. This study aimed to analyze the environmental, social, and educational aspects of the residential house on the outskirts of the river Melawi Lanting, particularly in the village of Tanjung Niaga District of Nanga Pinoh Melawi District, West Kalimantan. This study uses a qualitative method. This research is a qualitative descriptive study. Subjects in this study is the owner of the house in the village of Tanjung Niaga lanting District of Nanga Pinoh Melawi District, West Kalimantan. Data collection techniques used were observation, interviews, and documentation. Examination of the validity of the data were cross-checked, while the use of data analysis techniques for interactive analysis. Results of research have shown some important conclusions include A) Environmental Aspects seen from lanting building forms a uniform look with gable roof and rectangular shape of the building. B) The social aspect, some of life's problems at home lanting include. C) Aspects of education at home lanting the form of life skills.